Effect of Nitric Oxide Delivery Device on Tidal Volume Accuracy During Mechanical Ventilation at Small Tidal Volumes. - Ranallo, Courtney D.; Thurman, Tracy L.; Holt, Shirley J.; Frank-Pearce, Summer G.; Anderson, Michael P.; Heulitt, Mark J. (Respiratory Care, 2020)
BACKGROUND: Inhaled nitric oxide (INO) is used in infants as a therapy for elevated pulmonary vascular resistance. When INO is delivered at low tidal volumes, displayed inspiratory and expiratory volumes vary widely. We hypothesize that volume is removed by the sampling line during the ventilation cycle, and this results in a net volume loss at low tidal volumes. This study aimed to measure the volumes delivered and to assess the accuracy of displayed ventilator values using a test lung. METHODS: A test lung was connected to a ventilator and an INO delivery system. All tests were performed with stable mode settings across volumes of 18, 30, 42, and 60 mL. Flow measured with a pneumotachometer attached between the test lung and the circuit assessed the percent error between inspiratory and expiratory volumes measured by the pneumotachometer measured and displayed on the ventilator under various INO/sample line conditions to determine where and how much volume was being displaced. RESULTS: Displayed and measured inspiratory volumes had small variations between the INO/sample line conditions and baseline. However, expiratory volumes, with the sample line connected, exhibited large percent error values that increased (-14, -20, -27, and -34) as tidal volume decreased (60, 42, 30, and 18 mL) and error was significantly larger compared to baseline in all tidal volumes (P < .01) with and without INO delivery. CONCLUSIONS: We concluded that inspiratory volumes were not affected by INO delivery, but additional removal of volume in the expiratory phase of the breath cycle by the sampling line results in a large error in the displayed expiratory volume.